Comunicación interna y pymes comerciales: estudio de caso almacenes electro hogar. - Blacio Lopez, German Roberto (Machala: Universidad Tecnica de Machala, 2024)
This research examines the methods and channels of internal communication in Small and Medium Enterprises (SMEs), focusing on Almacenes Electro Hogar, a commercial company located in the province of El Oro, Ecuador. The company, which has 137 employees, has experienced significant growth since its founding in 2012. However, this growth has brought challenges in managing internal communication, which is the primary focus of this study. The research employs a mixed methodology, including interviews, surveys, and mapping of channels and communication flows to diagnose the current state of internal communication within the company. The results revealed a significant correlation between internal communication and productivity. It was observed that errors and barriers in communication hinder the work environment, negatively impacting business effectiveness. These findings highlight the importance of implementing strategies and actions to improve internal communication and the work climate at Almacenes Electro Hogar. Internal communication is a crucial process for cohesion and operational efficiency within an organization. It facilitates the flow of information between different hierarchical levels and departments, allowing for the transmission of instructions and policies from upper management to employees, while also fostering feedback, participation, and staff commitment to organizational objectives. Effective internal communication is essential for aligning members of the organization with its vision and mission, resolving conflicts, improving team morale, and promoting a collaborative work environment. In today’s context, where digital transformation and adaptation to change are constant, maintaining effective internal communication is even more crucial to ensure everyone is informed and aligned with the strategies and changes being implemented. Julka A. (2021) defines internal communication as the transmission, reception, and circulation of information among collaborators, which can occur through traditional or digital channels, whether written or oral. Martínez (2015) expands this definition to include information exchanges within an organization, encompassing downward messages (from management to employees), upward messages (from employees to management), and lateral messages (between colleagues). This process involves not only the transmission of information but also the construction of meanings and the formation of interpersonal relationships. Internal communication has become a fundamental pillar for the success of companies, especially for SMEs. The way an organization manages its internal information flows can significantly impact its performance, cohesion, and ability to adapt to changes. This research focuses on analyzing and proposing improvements in internal communication at Almacenes Electro Hogar, aiming to address the challenges and deficiencies identified. In the context of SMEs, where resources are limited and the organizational structure is less formal, internal communication becomes even more relevant. These companies rely heavily on the clarity and fluidity of information to coordinate activities, resolve problems, and make strategic decisions. Effective internal communication can enhance a sense of belonging and commitment among employees, which is crucial for the long-term success of the company. Martínez J. (2020) emphasizes that communication facilitates the basic functions of management: planning, organizing, directing, and controlling, allowing organizations to achieve their goals and overcome challenges. Almacenes Electro Hogar specializes in selling household appliances across several cantons in El Oro, including Machala, Pasaje, Santa Rosa, among others. With a team of 137 employees and significant growth in recent years, the company faces challenges in managing its internal communication. A preliminary diagnosis, based on participant observation within the company, identified deficiencies such as a lack of clear communication channels, inadequate feedback, and low employee participation in decision-making. These issues are not unique to Almacenes Electro Hogar but reflect a common trend in many rapidly growing SMEs that lack an adequate internal communication infrastructure. Ineffective communication can lead to misunderstandings, internal conflicts, and decreased productivity and job satisfaction. Therefore, it is essential to conduct an analysis to address these deficiencies and promote more effective communication within the organization. Martín, C. (2021) notes that many organizational problems are related to poor internal communication management, which can negatively impact the company’s image, productivity, and work climate. The study aims to identify the main barriers and challenges to develop a comprehensive strategy that includes appropriate channels, methods, and tools for improving internal communication at Almacenes Electro Hogar. It also seeks to determine methods for applying and evaluating the impact of the proposed improvements. The research will use a mixed methodology combining qualitative and quantitative techniques, starting with a literature review on best practices and theories in internal communication for SMEs. Following this, a diagnostic evaluation will be conducted at the company through surveys and interviews with employees and managers to assess various communication-related variables. Surveys will measure aspects such as message clarity, frequency, accessibility of information, and employee satisfaction with current communication channels. Qualitative interviews will provide a deeper understanding of perceptions and experiences related to current internal communication. Based on the results, a proposal for improvement will be developed, including implementing communication actions, training staff in communication skills, and creating clear policies and procedures for information management.
Esta investigación analiza los métodos y canales de comunicación interna en las Pequeñas y Medianas Empresas (PyMEs), centrando el estudio en Almacenes Electro Hogar, una empresa comercial ubicada en la provincia de El Oro, Ecuador. La empresa, que cuenta con 137 empleados, ha experimentado un crecimiento significativo desde su fundación en 2012. Sin embargo, este crecimiento ha generado desafíos en la gestión de la comunicación interna, que son el foco principal de este estudio. La investigación emplea una metodología mixta que incluye entrevistas, encuestas, y mapeo de canales y flujos comunicacionales para diagnosticar la situación actual de la comunicación interna en la empresa. Los resultados revelaron una correlación significativa entre la comunicación interna y la productividad. Se observó que los errores y barreras en la comunicación dificultan el ambiente laboral, lo que a su vez afecta negativamente la efectividad del negocio. Estos hallazgos subrayan la importancia de implementar estrategias y acciones para mejorar la comunicación interna y el clima laboral en Almacenes Electro Hogar. La comunicación interna es un proceso crucial para la cohesión y eficiencia operativa dentro de una organización. Facilita el flujo de información entre distintos niveles jerárquicos y departamentos, permitiendo la transmisión de instrucciones y políticas desde la alta dirección hacia los empleados, así como fomentando la retroalimentación, participación y compromiso del personal con los objetivos organizacionales. Una comunicación interna efectiva es esencial para alinear a los miembros de la organización con la visión y misión, resolver conflictos, mejorar la moral del equipo y promover un entorno de trabajo colaborativo. En el contexto actual, donde la transformación digital y la adaptación al cambio son constantes, mantener una comunicación interna eficaz es aún más crucial para asegurar que todos estén informados y alineados con las estrategias y cambios implementados. Julka A. (2021) define la comunicación interna como la transmisión, recepción y circulación de información entre colaboradores, que puede realizarse a través de canales tradicionales o digitales, ya sea de manera escrita u oral. Martínez (2015) amplía esta definición al incluir los intercambios de información descendentes (de la gerencia hacia los empleados), ascendentes (de los empleados hacia la gerencia) y laterales (entre colegas). Este proceso abarca no solo la transmisión de información, sino también la construcción de significados y la formación de relaciones interpersonales. La comunicación interna se ha convertido en un pilar fundamental para el éxito de las empresas, especialmente para las PyMEs. La forma en que una organización gestiona sus flujos de información internos puede influir notablemente en su rendimiento, cohesión y capacidad para adaptarse a cambios. Este trabajo de investigación se enfoca en analizar y proponer mejoras en la comunicación interna de Almacenes Electro Hogar, con el objetivo de abordar los desafíos y deficiencias identificadas. En el contexto de las PyMEs, donde los recursos son limitados y la estructura organizacional es menos formal, la comunicación interna es aún más relevante. Estas empresas dependen en gran medida de la claridad y fluidez de la información para coordinar actividades, resolver problemas y tomar decisiones estratégicas. Una comunicación interna eficaz puede fortalecer el sentido de pertenencia y compromiso entre los empleados, factores clave para el éxito a largo plazo de la empresa. Martínez J. (2020) destaca que la comunicación facilita las funciones básicas de administración: planificación, organización, dirección y control, permitiendo a las organizaciones alcanzar sus metas y superar desafíos. Almacenes Electro Hogar se dedica a la venta de electrodomésticos en varios cantones de El Oro, incluyendo Machala, Pasaje, Santa Rosa, entre otros. Con un equipo de 137 empleados y un crecimiento notable en los últimos años, la empresa enfrenta problemas en la gestión de su comunicación interna. Un diagnóstico preliminar, basado en la observación participante, identificó deficiencias como la falta de canales de comunicación claros, deficiencia en la retroalimentación y baja participación de los empleados en la toma de decisiones. Estos problemas no son únicos para Almacenes Electro Hogar, sino que reflejan una tendencia común en muchas PyMEs que crecen rápidamente sin establecer una infraestructura adecuada para la comunicación interna. La falta de comunicación efectiva puede llevar a malentendidos, conflictos internos y disminución de la productividad y satisfacción laboral. Por lo tanto, es crucial realizar un análisis que aborde estas deficiencias y promueva una comunicación más eficaz dentro de la organización. Martín, C. (2021) señala que muchos problemas dentro de las organizaciones están relacionados con una gestión inadecuada de la comunicación interna, lo que puede perjudicar la imagen, productividad y clima laboral de la empresa. El estudio propone identificar las principales barreras y desafíos para desarrollar una estrategia integral que incluya canales, métodos y herramientas adecuados para mejorar la comunicación interna en Almacenes Electro Hogar. También se busca determinar cómo aplicar y evaluar el impacto de las mejoras propuestas. Se utilizará una metodología mixta que combinará técnicas cualitativas y cuantitativas, comenzando con una revisión de la literatura sobre las mejores prácticas y teorías en comunicación interna en PyMEs. Posteriormente, se realizará una evaluación diagnóstica en la empresa mediante encuestas y entrevistas con empleados y directivos para valorar variables relacionadas con la comunicación. Las encuestas evaluarán aspectos como la claridad de los mensajes, frecuencia, accesibilidad de la información y satisfacción de los empleados con los canales actuales. Las entrevistas cualitativas ofrecerán una comprensión más profunda de las percepciones y experiencias respecto a la comunicación interna actual. Con base en los resultados, se elaborará una propuesta de mejora que incluirá la implementación de acciones comunicativas, capacitación del personal en habilidades comunicativas y la creación de políticas y procedimientos claros para la gestión de la información.
Keywords: COMUNICACIÓN INTERNA; PRODUCTIVIDAD; CLIMA LABORAL; PYMES COMERCIALES.